Perancangan sistem aplikasi penyewaan mobil bus berbasis web - Ritna Yohana Ginting; Agus Sulistyanto; Asih Septia Rini (Jurnal Manajamen Informatika Jayakarta, 2022)
The bus rental process currently running, there are several identified obstacles, namely for the purposes of making letters such as rental-rental letters, returning cars, business process reports and checking invoices which are still manual which takes a long time. The research objective is to design and build an online Bus Car Rental System. The benefit obtained from this research is that the system can facilitate the process of renting a bus car between tenants and the company in conducting transactions and recap data reports regarding rentals. In building a system using the SDLC system development method with the Waterfall method, for system modeling using UML (Unifield Modeling Language) and the software used in building this system using the PHP programming language and XAMPP as a connection to the database, namely MySQL. The data collection method used was observation, interviews and literature. The results of this study indicate that the use of an online-based bus car rental system can help simplify the transaction process, data processing such as financial data, bus data, driver data and bus tenant lists.